If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(k + -12) = 37 Reorder the terms: -1(-12 + k) = 37 (-12 * -1 + k * -1) = 37 (12 + -1k) = 37 Solving 12 + -1k = 37 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1k = 37 + -12 Combine like terms: 12 + -12 = 0 0 + -1k = 37 + -12 -1k = 37 + -12 Combine like terms: 37 + -12 = 25 -1k = 25 Divide each side by '-1'. k = -25 Simplifying k = -25
| p=3+20 | | -2-10z=-9z-9 | | 32-4y= | | t=-16t^2+1050 | | 3/5=x+1/9 | | -3-5(3x+6)=7 | | Y=-3.5+0.5y | | 11m-8-6m=-23 | | 8/h=11 | | 3=6(h-2)+17 | | x+2.23+x=5 | | 9(w-2)=48 | | 4/5x-x=5/10x-9/2 | | 5(x-1)=2x+4 | | -5t=19t | | 6v^2-18v=60 | | 2x+7=3x-x+8 | | 11-k=2.4(6.5-h) | | 5x+2(11-4x)=28+x | | 7(2x+4)-6x= | | 0.00238cg=mg | | 2=15z^2+x | | x-4*5=1 | | 4/x+6=5 | | 5x-7/3=6 | | 7(h+3)=6(h-30) | | 2(a+4)+15=13 | | 2(x+6)=-2(x-2) | | 2-9a=200 | | 8x+(6x/2)=154 | | 2r-7-4r=4r-7 | | 2d-8=-2d+8 |